IFS Approaches for Sustainable Livelihood of Small and Marginal Farmers in Odisha - B. Mishra, S.S. Nanda, R. Mishra, P.K. Panda (Indian Journal of Extension Education, 2022)
Agriculture is the main source of rural employment but being deprived of irrigation facilities a majority of small and marginal farmers are heavily under-employed for 6 to 8 months in a year in rain fed farming system. Even under well established irrigated condition the growth of agriculture sector itself has been almost stagnant for the last 8 to 10 years. Sustainable agriculture seeks to achieve three main goals, economic efficiency, environmental quality and social responsibilities. It is estimated that about 7 million hectares of land in this country is affected by varying degree of soil salinity and sodicity that inhibit the agriculture production in the affected areas. The farmers generally unaware of the magnitude of the problems continue to grow crops without soil reclamation measures, and harvest very poor yields. The rain fed farming comprises about 91% area coarse cereals, 91% of pulses and 80% of oilseeds and 65% of cotton besides supporting major animal production systems. The production and productivity is yet not up to the mark which necessitates an integrated intensive farming system that includes almost all the components of crop and allied agri-enterprises available or can be improved in the rain fed agriculture. This farming system approach which comprises not only crops, but also horticulture, livestock, fisheries and agro forestry is in practice by and large which needs improvement through the technology intervention in addition to the policy support. The farmers through their experience have established these farming systems to meet their food, fiber and fuel requirements in a manner that they are least dependant on the external sources. The study encompasses the effort to maximize the output from the land based enterprises comprising all possible combinations of the enterprises to have an appropriate cost effective farming system to make farming profession much more stable, sustainable and profitable benefiting the farming communities in general and resource poor farmers in particular. The issues of such intensive integrated farming system address rain fed agriculture/ farming with integrated watershed approach, cropping system approach, multistoried farming system, livestock cum cropping system, integrated agro forestry system, organic farming system, alternate farming system, integrated fish farming, shifting cultivation system, integrated crop management etc. to combat the effects of climate change issues and challenges in rain fed agriculture with reference to small and marginal farmers to generate sustainable livelihood.